Converting E-Learning Into M-Learning Application Using MMCD - Saifudin, W. S. N.; Salam, S.; Abdullah, M. H. L. (2011)
E-Learning system has dominated the internet-based distance education for the past two decades. With the advance of mobile technology, the use of mobile device as m-learning platform has now becoming a new way of e-learning that deliver knowledge at any time any place. However, the limitation of mobile devices compared to computers give challenges to the developers in developing good m-learning applications. Aspects such as content design, navigation design and mobile HCI are critical and need extra attention during the development phase. MMCD is a set of development framework and methodology designed for multimedia mobile content development using Flash Lite technology. This research will present the MMCD framework and methodology for converting e-learning application into m-learning application to ease and guide the development process.